(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To compare the efficacy of coblation tonsillectomy and dissection tonsillectomy regarding the duration of surgery, amount of intraoperative bleeding, postoperative pain, recovery time and complications. Methods: 50 patients aged 5-30 years with chronic tonsillitis who underwent tonsillectomy operation were randomly divided into two groups. One group underwent coblation tonsillectomy while other group with dissection tonsillectomy. Chronic tonsillitis patients with adenoid hypertrophy and Otitis media with effusion were excluded by diagnostic nasal endoscopy, imaging and audiometry. All patient were examined regularly after surgery for 10 days to assess the postoperative morbidity and efficacy of both coblation and dissection methods. Duration of surgery, amount of intraoperative bleeding, recovery time, postoperative pain& requirement of analgesics, time required to regain normal diet & activityand complication were assessed. Result: Comparing the coblation tonsillectomy to cold dissection group the mean duration of surgery was 9.7 versus 18.4 minutes, the amount of intra operative bleeding 10.62 versus 28.72 milliliter. The difference on the postoperative pain scale, requirement of analgesics, condition of the tonsillar fossa, time required to regain normal diet & activity between two groups were statistically significant. Conclusion: In our study patient underwent coblation tonsillectomy providing a near bloodless field, minimum operating time, less postoperative pain, quicker return to normal diet, normal activity and less use of analgesics than patients underwent dissection tonsillectomy. Postoperative morbidity and complications were lower as compared to conventional cold dissection technique. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 121-127